Self-medication by orang-utans (Pongo pygmaeus) using bioactive properties of Dracaena cantleyi. Issue 1 (December 2017) - Morrogh-Bernard, H.; Foitová, I.; Yeen, Z.; Wilkin, P.; Martin, R.; Rárová, L.; Doležal, K.; Nurcahyo, W.; Olšanský, M.
Abstract Animals self-medicate using a variety of plant and arthropod secondary metabolites by either ingesting them or anointing them to their fur or skin apparently to repel ectoparasites and treat skin diseases. In this respect, much attention has been focused on primates. Direct evidence for self-medication among the great apes has been limited to Africa. Here we document self-medication in the only Asian great ape, orang-utans (Pongo pygmaeus ), and for the first time, to our knowledge, the external application of an anti-inflammatory agent in animals. The use of leaf extracts fromDracaena cantleyi by orang-utan has been observed on several occasions; rubbing a foamy mixture of saliva and leaf onto specific parts of the body. Interestingly, the local indigenous human population also use a poultice of these leaves for the relief of body pains. We present pharmacological analyses of the leaf extracts from this species, showing that they inhibit TNFα-induced inflammatory cytokine production (E-selectin, ICAM-1, VCAM-1 and IL-6). This validates the topical anti-inflammatory properties of this plant and provides a possible function for its use by orang-utans. This is the first evidence for the deliberate external application of substances with demonstrated bioactive potential for self-medication in great apes.